The Effect Of Brand Image, Quality Products And Price On Samsung Handphone Decision Purchase - Della Nuril M; Yuniorita Indah Handayani (ABM: International Journal of Administration, Business and Management, 2019)
This study aims to determine the effect of Brand Image either together or partially or to know the variables that affect consumer purchasing decisions. Independent variables used in this study are brand image (X1), Product Quality (X2) and Price (X3) while the dependent variable is Purchase Decision (Y). The research method used in this research is quantitative research method by using sample of 50 respondents of STIE Mandala Jember Students. Data analysis method used in this research is descriptive analysis method and multiple linear regression analysis. Data processing is done by using computer software SPSS 20 for windows. Keywords: Brand Image, Product Quality, Price and Purchase Decision